2021
DOI: 10.1002/pmrj.12649
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:Running‐related injuries in middle school cross‐country runners: Prevalence and characteristics of common injuries

Abstract: Background: Understanding the prevalence and factors associated with running-related injuries in middle school runners may guide injury prevention. Objective: To determine the prevalence of running-related injuries and describe factors related to a history of injury. Design: Retrospective cross-sectional study. Setting: Survey distributed online to middle school runners. Methods: Participants completed a web-based survey regarding prior runningrelated injuries, training, sleep, diet, and sport participation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Furthermore, it is bilateral in 20–30% of cases [ 22 , 23 ]. It has also been reported among practitioners of other sports that feature explosive, anaerobic and acyclic components and continuous changes of direction, such as basketball, sports gymnastics, volleyball, karate, taekwondo, baseball and running, as well as among people who practice multiple sports [ 24 , 25 , 26 , 27 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Furthermore, it is bilateral in 20–30% of cases [ 22 , 23 ]. It has also been reported among practitioners of other sports that feature explosive, anaerobic and acyclic components and continuous changes of direction, such as basketball, sports gymnastics, volleyball, karate, taekwondo, baseball and running, as well as among people who practice multiple sports [ 24 , 25 , 26 , 27 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Anxiety can interfere with rehabilitation progress in athletes [ 17 ]. Cross sectional studies in adolescent and adult runners show that running-related injury is also related to wellbeing and various QOL indicators like sleep and days without musculoskeletal pain [ 18 , 19 ]. Despite these emerging relationships, the current clinical paradigm for running injury still primarily focuses on physical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Shin splint prevalence among young girls and boys was found to be up to 13.6 percent in a research by Alexander C. Wu done in the United States in 2020, compared to a 5.9 percent higher incidence among women. (19) In a 2016 research by Sadiya Sultana et al in Bangladesh, it was shown that more over one-quarter (25.9%) of male athletes from several reputable clubs were suffering from shin splints, while 3.4% had a history (ever prevalence) of the condition. (6) 17.9% of people filled out the MTSS questionnaire to rate the severity of shin splints.…”
Section: Discussionmentioning
confidence: 99%